A Study On Factors Affecting Students’ Speaking Ability (The Case Of The Students Of SMP Katolik Pelita Bangsa Makale Tana Toraja, Academic Year 2011/2012) - Selvi Panggua (AgroSainT, 2012)
This research was a case study that aimed to know factors affecting the students’ ability to speak English. The case was refers to the students of SMP Katolik Pelita Makale Tana Toraja, Academic Year 2011/2012. This research hoped to provide supporting material to handle students in speaking English both in the classroom as well as in their daily communication. The population of this study was the students of SMP Katolik Pelita Makale Tana Toraja, Academic Year 2011/2012. The total number of population was 242 students, which scattered in seven classes. The data was collected using a snowball technique. Therefore in this research there was not sampling limitation. To obtain the factors that affecting students’ speaking ability, this study used observations and interview. Observation was intended to find a general overview of learning and teaching and the use of English in the school. While the interview was given to the students to find data of factors that affect their ability to speak English. In processing the findings data, the writer used description qualitative method. The result of the research showed that there were factors that affecting the students of SMP Katolik Pelita Bangsa Makale Tana Toraja in speaking English. The finding factors were consisted of interest, self-motivation, confidence and hesitation, the performance of the teacher in English language learning, support and enhancement programs related with English in the school, the opportunity to memorize and practice the English language, and the supports of family and the society. From the result of the research above, it can be concluded that the factors affecting students’ speaking ability classified into two factors. They are, internal factors: interest, self-motivation, confidence, and hesitation. External factors: the English teacher performance, support and enhancement programs of school related with English, and the family or community support.